From boron clusters to gold clusters: new label-free colorimetric sensors. Issue 86 (16th October 2017) - Qi, Bin; Wu, Chenchen; Xu, Ling; Wang, Wenjing; Cao, Jin; Liu, Jun; Zhang, Shuai; Gabel, Detlef; Zhang, Haibo; Zhou, Xiaohai
Abstract : Based on boron clusters, AuNPs were successfully prepared and exhibited high performance in phase transfer and heavy-metal ion sensing. Abstract : A fundamental boron cluster, [ closo -B12 H12 ] 2−, mainly known as an inert agent for boron neutron capture therapy, can also serve as a bi-functional reductant and a capping agent for the formation of monodispersed size-controlled gold nanoparticles (AuNPs) under mild reaction conditions. The obtained AuNPs remained thermo-dynamically stable over 3 months, and exhibited high performance in phase transfer and sensing of heavy metal ions.